Republic of Armenia : 2021 Article IV Consultation, Fourth and Fifth Reviews Under the Stand-By Arrangement, and Request for Waiver of Nonobservance of Performance Criterion and Monetary Policy Consultation Clause-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Armenia. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2021)
Armenia has commenced a robust recovery from the deep 2020 recession, benefiting from strong policies and the lifting of the political uncertainty after the elections in June. A gradual but uneven improvement in the pandemic situation, pent-up demand, and the strengthening of public and private investment are expected to drive 2022 growth. Robust growth is expected over the medium term. Risks. Risks are relatively balanced, although uncertainty remains high. Strong reform implementation and accelerating vaccinations could improve the outlook, while risks of a protracted pandemic, renewed geopolitical tensions, a slowdown in major trading partners, and stress from global financial volatility and/or trade tensions could hamper the recovery.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Armenia, Republic of